스토리를 활용한 효과적인 어휘지도방법 : 명시적 또는 암시적 지도방법 - Shin Hae Lee (The Graduate School, Ajou University, 2015)
The goal of this study is to research the effects of explicit and implicit vocabulary instructions using stories on sixth grade students’ vocabulary acquisition and motivation of learning English. There were 59 elementary school students who participated in this study. Nation’s vocabulary test for checking homogeneity, and pre and post vocabulary tests for estimating vocabulary ability were conducted to collect data. Also, pre and post surveys were given to investigate students’ motivation of learning English. Independent sample t-tests and paired t-tests were implemented for analysis of the data. This study showed that explicit vocabulary instruction using stories is more effective than implicit vocabulary instruction using stories on vocabulary learning. Moreover, the result of the survey proved the positive effects of explicit vocabulary instruction using stories on the sixth grade students’ motivation of learning English. The specific results of this study are the following: 1) The amount of vocabulary acquisition of the explicit vocabulary instruction group was higher than that of the implicit vocabulary instruction group. 2) Students in the explicit vocabulary instruction group showed higher motivation of learning English than students in the implicit vocabulary instruction.
학위논문(석사)--아주대학교 교육대학원 :TESOL,2015. 2
Keywords: 스토리; 어휘; 지도